ENGLISH STUDENTS’ STRATEGIES IN ANSWERING THE TOEFL LISTENING COMPREHENSION - Wiranti Rahayu; Santi Farmasari; Ni Wayan Mira Susanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to investigate English students’ strategies in answering TOEFL Listening Comprehension questions at the University of Mataram. This research employed a qualitative approach with purposive sampling, involving three students of the English Education Program who achieved a minimum listening score of 50. Data were collected through in-depth interviews and supported by documentation, and analyzed using the interactive model of data condensation, data display, and conclusion drawing. The findings reveal that students encountered various difficulties, including linguistic factors (fast speech, accent variation, and intonation), cognitive factors (difficulty maintaining concentration), limited vocabulary, challenges in interpreting implied meaning, external factors (noise and poor audio quality), and affective factors (anxiety and lack of confidence). To overcome these difficulties, students applied several strategies, such as focusing on main ideas and keywords, using prediction, visualization, paraphrasing, and note-taking, as well as engaging in self-directed practice through online resources. The findings also indicate that students combined strategies recommended by ETS with their personal learning approaches. The selection of these strategies was influenced by the need to manage fast speech, reduce cognitive load, enhance memory retention, minimize confusion in answering questions, and increase exposure to listening materials. Overall, students’ strategy use was adaptive and shaped by their learning experiences and perceived effectiveness.